2012
DOI: 10.1179/1743676111y.0000000062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Al2O3nanopowders characterised by various physicochemical properties on growth of green algaScenedesmus quadricauda

Abstract: This study estimates the influence of five Al 2 O 3 nanopowders on the growth of Scenedesmus quadricauda depending on the physical and chemical properties of the alumina nanoparticles and on the concentration of the nanopowder. The agglomeration and crystallisation levels of the alumina nanopowders as well as the zeta potential, the conductivity and the pH of nanopowderscontaining growth media are considered. The strongest algal growth inhibiting effect was accompanied by the highest degree of agglomeration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…54 The probable mechanism of action that should be considered for the analyses nanocomposite materials is the presence of different ceramic oxide and noble metal components is the surface-dissolution of as well as physical interaction with algae cells. 46,53,58 Ti 3 C 2 /Al 2 O 3 / Ag nanoparticles stimulated algal growth, with an increasing effect being caused by higher nanoparticle concentrations. The results obtained for Ti 3 C 2 /SiO 2 /Ag indicated both slight inhibition/stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 The probable mechanism of action that should be considered for the analyses nanocomposite materials is the presence of different ceramic oxide and noble metal components is the surface-dissolution of as well as physical interaction with algae cells. 46,53,58 Ti 3 C 2 /Al 2 O 3 / Ag nanoparticles stimulated algal growth, with an increasing effect being caused by higher nanoparticle concentrations. The results obtained for Ti 3 C 2 /SiO 2 /Ag indicated both slight inhibition/stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of characteristic aggregates entrapping algal cells was revealed for nano-TiO 2 . 45 The experiment carried out by Karwowska et al 46 on Al 2 O 3 nanopowders' inuence on green algae Scenedesmus quadricauda revealed that aer 7 days the algal growth was inhibited by 5-54% in nanopowder concentrations of 500 mg l À1 , while in concentrations of 1000 mg l À1 it reached 39-69%, depending on the properties of the individual nanopowder. Marine phytoplankton, including Thalassiosira pseudonana, Skeletonema marinoi, Dunaliella tertiolecta, and Isochrysis galbana, were also affected by metal oxide nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have also attempted to utilize nano-Al 2 O 3 as a coagulant in wastewater treatment as well as a component in the removal of organic matter [ 1 ]. As these applications release nano-Al 2 O 3 into the environment, especially aquatic environments, they may have an impact on aquatic organisms in these environments [ 2 , 3 ]. The toxicity of nano-Al 2 O 3 has been investigated with different organisms, such as bacteria, zooplankton, and phytoplankton [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…According literature data and our earlier phase studies, aluminum oxide nanopowders prepared from alumina precursors obtained by exposure of trimethyl-and triethyl aluminum solutions to oxygen and moisture from air were mixtures of σ-Al 2 O 3 , ␥-Al 2 O 3 , -Al 2 O 3 and amorphous phases [10,16].…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, it has been reported that the morphology of alumina nanopowders obtained by this method depends on the time of Et 3 Al exposure to air [10]. However, methodical studies on reaction conditions influencing the morphology of alumina powders obtained from aluminum trialkyls have not been carried out.…”
Section: Introductionmentioning
confidence: 99%